Psychometric Analysis of the Professional Identity Questionnaires in Croatian Nursing Student Context. (October 2021) - Gusar, Ivana; Tokić, Andrea; Lovrić, Robert
Introduction: The identification of nursing students with their profession, as well as gained professional competencies, are the crucial factors of the quality of their future work activities and the level of safety of the patient they are taking care of. Therefore, it is of utter importance to estimate the nursing students' professional identity during their education.Objectives: The purpose of this study was to translate Professional Identity Five-Factor Scale and Identity questionnaire, to test their psychometric properties in Croatian practice and to identify more suitable instrument of measuring the level of nursing students' professional identity in Croatian context.Methods: Quantitative, cross-sectional two-phase study was performed. In the first phase translated questionnaires were administered to a sample of 432 nursing students. Based on the confirmatory factor analysis (CFA), which revealed poor model fit, the principal component analysis was conducted. In the second phase, CFA was used to test the Croatian version of the instruments' factor structure on a sample of 222 students with different study orientations.Results: The CFA results, conducted in first phase, do not support the original version of the factor structures of the Professional Identity Five-Factor Scale and Identity models. The exploratory approach showed that the translated Professional Identity Five-Factor Scale had three factors with good psychometric properties explaining 49.35% of the variance. Translated Identity questionnaire had a two-factor structure (63.46% explained variance) with good reliability properties. In the second phase, on another heterogeneous sample of students, the described factor structure was found to have a good model fit obtained by CFA.Conclusions: According to the findings, Professional Identity Five-Factor is more appropriate for evaluating professional identity of nursing students, and Identity is probably better suited to measure professional identity among working professionals.